2020
DOI: 10.1097/iae.0000000000002632
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Masked, Randomized, Sham-Controlled, Single-Center Study With Photobiomodulation for the Treatment of Dry Age-Related Macular Degeneration

Abstract: Purpose: The LIGHTSITE I study investigated the efficacy and safety of photobiomodulation (PBM) treatment in subjects with dry age-related macular degeneration. Methods: Thirty subjects (46 eyes) were treated with the Valeda Light Delivery System, wherein subjects underwent two series of treatments (3• per week for 3-4 weeks) over 1 year. Outcome measures included best-corrected visual acuity, contrast sensitivity, microperimetry, central drusen volume and drusen thickness, and quality of life assessments. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 35 publications
(50 reference statements)
3
80
0
Order By: Relevance
“…The mean 1 and 3 mm ETDRS circle manually corrected drusen volume determined by Heidelberg SD-OCT was significantly different from the Zeiss SS-OCT assessed and manually corrected 1 and 3 mm ETDRS circle drusen volume with a moderate correlation (mean difference: 0.1231 ± 0.0371 mm 3 , p-value ≤ 0.001, corr. p ≤ 0.001, correlation of r = 0.681) ( Figure 4A).…”
Section: Inter-device Comparison Using Manufacturer Softwarementioning
confidence: 60%
See 2 more Smart Citations
“…The mean 1 and 3 mm ETDRS circle manually corrected drusen volume determined by Heidelberg SD-OCT was significantly different from the Zeiss SS-OCT assessed and manually corrected 1 and 3 mm ETDRS circle drusen volume with a moderate correlation (mean difference: 0.1231 ± 0.0371 mm 3 , p-value ≤ 0.001, corr. p ≤ 0.001, correlation of r = 0.681) ( Figure 4A).…”
Section: Inter-device Comparison Using Manufacturer Softwarementioning
confidence: 60%
“…In the Zeiss SS-OCT there was no significant difference between manufacturer automated assessment? mean 1 and 3 mm ETDRS circle drusen volume and manually corrected mean 1 and 3 mm ETDRS circle drusen volume (mean difference: 0.0001 ± 0.0003 mm 3 , p = 0.262, corr. p = 0.524, r = 1.0).…”
Section: Intra-device Comparison Before and After Manual Correctionmentioning
confidence: 96%
See 1 more Smart Citation
“…The antioxidants reduce RPE damage by limiting the generation of free radicals, protecting photoreceptors and acting as retinal tissue nutrients [ 66 ]. In addition, recent single-center studies showed that photobiomodulation, a recently proposed light therapy, improved symptoms and reversed pathological changes (drusen formation) without causing harmful effects [ 67 , 68 ], suggesting a novel strategy for the earlier stage of AMD.…”
Section: Prevention and Intervention Strategies Of Amdmentioning
confidence: 99%
“…Markowitz et al recently used PBM therapy to treat patients with the dry (more common and difficult to treat) form of macular degeneration. They found that application of multiple wavelengths (590, 660, 850 nm) over a year, compared to a sham treatment, significantly reduced the volume of central drusen and improved visual function [154].…”
Section: Photobiomodulation Effects On Human Healthmentioning
confidence: 99%